1999
DOI: 10.1038/sj.bjp.0702859
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of sibutramine‐induced increases in extracellular noradrenaline concentration in rat frontal cortex and hypothalamus by α2‐adrenoceptors

Abstract: 1 The eects of sibutramine (0.25 ± 10 mg kg 71 i.p.) on extracellular noradrenaline concentration in the frontal cortex and hypothalamus of freely-moving rats were investigated using microdialysis. The role of presynaptic a 2 -adrenoceptors in modulating the eects of sibutramine in these brain areas was also determined. 2 Sibutramine induced an increase in extracellular noradrenaline concentration, the magnitude of which paralleled dose, in both brain areas. In the cortex, this increase was gradual and sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…On the other hand, the changes caused by MA uptake inhibitors in the MA level in cerebral tissue were statistically almost insignificant [17,22,24,26,28]. Wortley et al and we have already reported that sibutramine strongly inhibited reuptake of 5-HT, norepinephrine and dopamine in mice in vivo, and caused large increases in extracellular 5-HT and norepinephrine levels and a small increase in the dopamine level, as measured by microdialysis, in the hypothalamus and striatum of rats [28,33,44]. Inhibitory effects of sibutramine on this MA reuptake have also been confirmed by in in vitro studies [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the changes caused by MA uptake inhibitors in the MA level in cerebral tissue were statistically almost insignificant [17,22,24,26,28]. Wortley et al and we have already reported that sibutramine strongly inhibited reuptake of 5-HT, norepinephrine and dopamine in mice in vivo, and caused large increases in extracellular 5-HT and norepinephrine levels and a small increase in the dopamine level, as measured by microdialysis, in the hypothalamus and striatum of rats [28,33,44]. Inhibitory effects of sibutramine on this MA reuptake have also been confirmed by in in vitro studies [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is of an interest to determine whether the food intake suppression by acute administration of sibutramine to normal rats is attributable to effects of this agent mediated by the VMH and ARC or effects of this agent in other brain areas, e.g., the LH and PVN, etc., and whether sibutramine acts on these hypothalamic nuclei to activate the sympathetic nervous system to increase energy expenditure [16,19,20,44].…”
Section: Introductionmentioning
confidence: 99%
“…NA is taken up by the NA transporter found exclusively on the neuronal membrane of noradrenergic cells (Lorang et al, 1994). Activation of terminal a 2 -adrenoceptors by the endogenous transmitter or exogenous receptor agonists reduces NA release (L'Heureux et al, 1986;Starke, 1977;Westfall, 1977), whereas blockade of these receptors has the opposite effect (Dennis et al, 1987;Gobert et al, 1997;Mateo et al, 1998;Wortley et al, 1999). Somatodendritic a 2 -adrenoceptors, by controlling the firing activity of NA neurons of the LC (Cedarbaum and Aghajanian, 1976;Svensson et al, 1975), contribute to the regulation of action potential-dependent release of NA (Florin-Lechner et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results for norepinephrine release in frontal cortex were recorded by Hudson et al (54), who further showed augmented release of norepinephrine in ventral hippocampus, and dopamine in the striatum. RX 821002 also enhances norepinephrine release in frontal cortex after administration of the uptake blocker sibutramine (115). Direct application of the antagonist to locus coeruleus induces a large increase in norepinephrine output in the cingulate cortex per se (72), and augments the norepinephrine releasing action of desipramine in the same area (74).…”
Section: Release Of Monoamines In the Cns And Behaviormentioning
confidence: 99%